EFFECTS OF NON-COMPLIANCE TO LLIN AND IPT IN PREGNANCY ON MATERNAL AND NEONATAL MALARIA, AGE AND BIRTH WEIGHTS OF NEONATES AT UYO - Ikpeze; Esu (International Journal of Research -GRANTHAALAYAH, 2016)
Pregnant mothers and children under 5 years are most vulnerable to Plasmodium falciparum malaria in Nigeria. Non-compliance to LLIN and IPT, and resultant maternal and cord blood malaria on neonatal age and birth weights were studied in Uyo, Nigeria between September and October 2013. Peripheral and cord blood from 106 consenting pregnant women were examined for malaria parasites; and their usage of LLIN and IPT ascertained. Ages and weights of resulting neonates were recorded at birth. Results showed that maternal and neonatal malaria infection rates (IR) were 54.7% (Mean± SD=49.23±26.41) and 45.3% (Mean± SD=40.6±20.6), with indications that maternal immunity increases with parity. Generally 29.2% and 39.6% of all neonates were respectively delivered pre-term and underweight. About 53.8% and 51.9% of the women were non-compliant to LLIN and IPT, respectively; and 91.4% of LLIN non-compliant as well as 94.8% of IPT non-compliant were infected with malaria. We inferred that use of LLIN and IPT would have offered the women protection against malaria. Heat generation, fear of toxic reactions, and difficulty in setting-up LLIN as well as ‘not sick’, fear of abortion, and doubtful efficacy of IPT were among the reasons given by pregnant women for non-compliance. Sustained health education on the use of LLIN and IPT will help to reduce malaria infection and its consequences in Uyo.